Hubungan antara Tingkat Kecemasan dengan Kualitas Tidur pada Pasien Compos Mentis di Ruang ICU - Indah Puji Lestari; Wahyu Endang Setyowati; Dwi Heppy Rochmawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Patients admitted to the Intensive Care Unit (ICU) often experience physiological disturbances caused by both medical conditions and intensive treatment procedures. One of the most common problems encountered is sleep disturbance. Several factors contribute to poor sleep quality in ICU patients, including repeated medical procedures, environmental noise from medical equipment and staff activities, discomfort due to body positioning, frequent interactions with health workers, continuous exposure to lighting, pain, and the underlying disease process. Persistent sleep disturbances can delay the healing process, increase blood pressure, and even elevate the risk of stroke. This study aimed to analyze the relationship between anxiety levels and sleep quality in compos mentis patients in the ICU of Sultan Agung Islamic Hospital Semarang. The research design employed a correlational approach with a cross-sectional method. A total of 30 respondents were selected according to the inclusion criteria. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality and the Hamilton Anxiety Rating Scale (HARS) to assess anxiety levels. The Chi-Square test was used for statistical analysis. The results showed an equal distribution of male and female respondents (15 each). Ten respondents had a post-laparotomy medical diagnosis, and the majority belonged to the late elderly age group (10 respondents). Most respondents experienced moderate anxiety (18 respondents), while poor sleep quality was reported by 17 respondents. The Chi-Square test revealed a p-value of 0.001, indicating a significant relationship between anxiety levels and sleep quality. In conclusion, higher anxiety levels were associated with poorer sleep quality among compos mentis patients in the ICU. These findings highlight the importance of nursing interventions that address both the physical and psychological aspects of patients to improve sleep quality and support recovery.